Gen Z and Group Work : How Communication Styles Affect Free-Riding Behaviours - Chuah, Kee Man; Radina, Mohamad Deli; Ch'ng, Looi Chin (Penerbit UKM, 2025)
This study examines the effect of communication styles on free-riding behaviours in group work among Generation Z (Gen Z) undergraduate students. A mixed-methods approach was employed, which included quantitative survey data from 186 undergraduate students in Malaysia and qualitative insights gathered from 24 students through focus groups. Findings indicate significant differences in free-riding experiences across groups with varying communication styles. Students exhibiting passive and passive-aggressive communication styles were noted to have higher levels of free-riding behaviours. Conversely, those demonstrating assertive communication showed substantially lower instances of free riding. Qualitative analysis further reveals the influence of technology preferences, conflict avoidance, and accountability challenges on the prevalence of free-riding behaviours. Digital communication, as favoured by this generation combined with a tendency to avoid confrontation, was found to increase unequal participation in group tasks. The study demonstrates the significance of creating a structured environment with clear expectations to address free-riding behaviours. There is also a need to establish ways to promote transparent collaboration practices beyond peer evaluation to enhance the effectiveness of group work. These findings contribute to developing pedagogical strategies to improve collaborative learning experiences and prepare Generation Z students for successful teamwork in both academic and professional contexts.